Metabiotics: One Step ahead of Probiotics; an Insight into Mechanisms Involved in Anticancerous Effect in Colorectal Cancer - Sharma, Mridul; Shukla, Geeta (Frontiers in Microbiology, 2016)
Colorectal cancer is closely associated with environment, diet and lifestyle. Normally it is treated with surgery, radiotherapy or chemotherapy but increasing systemic toxicity, resistance and recurrence is prompting scientists to devise new potent and safer alternate prophylactic or therapeutic strategies. Among these, probiotics, prebiotics, synbiotics and metabiotics are being considered as the promising candidates. Metabiotics or probiotic derived factors can optimize various physiological functions of the host and offer an additional advantage to be utilized even in immunosuppressed individuals. Interestingly, anti colon cancer potential of probiotic strains has been attributable to metabiotics that have epigenetic, antimutagenic, immunomodulatory, apoptotic and antimetastatic effects. Thus, it’s time to move one step further to utilize metabiotics more smartly by avoiding the risks associated with probiotics even in certain normal / or immuno compromised host. Here an attempt is made to provide insight into the adverse effects associated with probiotics and beneficial aspects of metabiotics with main emphasis on the modulatory mechanisms involved in colon cancer.